The emerging principles of international competition law - Noonan, Chris (Oxford University Press, 2008)
Noonan analyses the legal and policy issues associated with the control of restrictive business practices and anticompetitive mergers in international markets. The book discusses international cartels, dumping, private market access barriers, and mergers between international firms subject to multi-agency review. Subjects covered include the harmonization and coordination of competition laws, cooperation between enforcement agencies, international judicial assistance, and the role of trade agreements and the World Trade Organization in international competition law. Noonan also examines the problems that States have in regulating conduct beyond their borders and the merits of a variety of potential responses